The Effect of Three Irrigants on the Coronal Leakage of the Root Canals System Irrigants - Zare Jahromi, Maryam; Barekatain, Mehrdad; Ebrahimi, Maziar; Askari, Bahare (Iranian Endodontic Journal, 2010)
INTRODUCTION: The production of smear layer during canal instrumentation is thought to increase coronal microleakage even after canal obturation. Previous studies have shown that the type of irrigant does not necessarily affect the seal of the obturation. Our study aimed to evaluate the effect of three irrigation solutions (MTAD, citric acid and EDTA/NaOCl) on the coronal microleakage of root canals. MATERIALS AND METHODS: Fifty five intact single rooted teeth were instrumented and randomly divided into three experimental groups (15 teeth each) and two control groups (5 teeth each). Final irrigation was carried out with MTAD in group I, citric acid in group II, and EDTA/NaOCl in group III. EDTA/NaOCl was used for the negative control group and saline irrigation was carried out in the positive control group. After lateral compaction with gutta-percha, the access cavities of the experimental specimens were restored with temporary restorative material. Temporary cement was not used in the positive control group. In the negative control group, access cavities and foramen apices were sealed with glass ionomer. Microleakage of samples was measured using the dye penetration technique. Data were analyzed with ANOVA and Tukey test to determine statistical differences between groups. RESULTS: MTAD, citric acid and EDTA/NaOCl all had less microleakage compared to normal saline. However, no difference was detected between the experimental groups. CONCLUSION: In this study, all three groups demonstrated effective seal with gutta-percha obturation. This is likely to be due to various factors including their ability to remove smear layer.